RELIABILITY ANALYSIS OF UNISTAR HR EM TYPE ELECTRIC SWITCH MACHINE AT MAROS STATION - Asmawaty Azis; Agus Miftakul Khoiri; Kurniawan Harun Rasyid (Jurusan Pendidikan Teknik Elektro, 2025)
Railway transportation requires an integrated and reliable system to ensure the safety and smoothness of train travel. This study aims to investigate the reliability of Unistar HR EM type electric switch machines at Maros Station in maintaining train travel safety. The research method used is reliability analysis using visual inspection, indicator measurement, and functional testing methods with 60 trial runs. The results show that the condition of the switch plate that has not been lubricated can increase friction and disrupt the performance of the electric switch machine. Based on the reliability calculation results, the lowest reliability value among the five switches is the W0421 electric switch machine, which is 93%. This indicates that there are still several indicators that do not meet the standard reference values, which can cause significant disruptions in the long term.